Altered awareness of action in Parkinson’s disease: evaluations by explicit and implicit measures - Naho Saito (Nature Portfolio, 2017)
Abstract Deficits in the integration of motor prediction and its feedback have been reported in Parkinson’s disease. Conscious awareness of action is proposed to emerge under the integration of motor prediction and its feedback. Thus, it may lead to changes in the awareness of the authorship of action (in other words, the sense of agency) in Parkinson’s disease. We have employed both explicit and implicit measures to assess the awareness of action in Parkinson’s disease and matched controls. As an explicit measure, an action recognition task requiring explicit judgments was used. Patients showed less attribution of their movements to non-biased and angular-biased visual feedbacks. As an implicit measure, the temporal attraction between the perceived time of actions and their effects, which is known as intentional binding task, was used. While action-effect association was observed in the control group, actions were not experienced as having shifted towards their subsequent effects in the patient group. These tendencies were consistent regardless of the side of the asymmetrical motor symptoms. These results may reflect an underlying abnormality in the awareness of voluntary action in Parkinson’s disease.